2002
DOI: 10.1007/s00428-001-0591-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Epstein-Barr virus in primary adenocarcinoma of the lung with Signet-Ring cells

Abstract: The Epstein-Barr virus (EBV) is directly implicated in the pathogenesis of a variety of undifferentiated carcinomas and has also been identified in conventional adenocarcinomas of the stomach. To date, the association of EBV with non-small cell lung carcinoma is restricted to Asian patients. To evaluate the presence of EBV in lung cancers from Europeans, we investigated primary lung adenocarcinomas with a similar morphological tumour pattern to those of the stomach, specifically rare tumours with components of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…13,12 However, the neoplastic cells had an extremely low 7 LMP1 expression, and in situ hybridization for EBV early RNA (EBER) and clonal episomal EBV sequences have been demonstrated in tumour tissue, but only in Asian 9,23,12,25,26 and in two caucasic patients. 18,19 We agree with these data because our five cases of pure lymphoepitheliomalike carcinomas have been negative for EBV.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…13,12 However, the neoplastic cells had an extremely low 7 LMP1 expression, and in situ hybridization for EBV early RNA (EBER) and clonal episomal EBV sequences have been demonstrated in tumour tissue, but only in Asian 9,23,12,25,26 and in two caucasic patients. 18,19 We agree with these data because our five cases of pure lymphoepitheliomalike carcinomas have been negative for EBV.…”
Section: Discussionsupporting
confidence: 86%
“…16 Only two pulmonary-carcinoma EBV associated in Caucasian patients have been recently reported. 18,19 Otherwise, several cases of lymphocyte rich adenocarcinomas but without EBV association have been also reported. 27,15 We describe 12 lung carcinomas (4 squamous-cell carcinomas and 8 adenocarcinomas) in an occidental population, all of them with EBV sequences in tumoral tissue demonstrated by PCR and/or EBER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 We studied Epstein-Barr virus RNA in 78 cases of pulmonary nonlymphoepitheliomalike carcinoma using in situ hybridization methodology in 1992, and found none of them to be positive for Epstein-Barr virus. 15 In contrast, several recent studies reported that Epstein-Barr virus gene products were detected in pulmonary nonlymphoepithelioma-like carcinoma, such as pulmonary squamous cell carcinoma and neuroendocrine carcinoma 13 and small-cell carcinoma of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are few reports demonstrating EpsteinBarr virus infection in pulmonary carcinoma in Western populations. Huber et al 12 reported a case of pulmonary adenocarcinoma with signet-ring-cell features harboring Epstein-Barr virus by EBER-1 in situ hybridization and BamHI W region polymerase chain reaction methods. Using Epstein-Barr virus nuclear antigen-1 immunohistochemistry, Grinstein et al 13 recently found that two of the 22 cases of pulmonary squamous-cell carcinoma and two of the 10 cases of pulmonary neuroendocrine carcinoma were positive for Epstein-Barr virus.…”
mentioning
confidence: 99%